A Study on the Application of Two Different Material Constitutive Models Used in the FE Simulation of the Cyclic Plastic Behavior of a Steel Beam-Column T-Stub Connection. (8th February 2021) - Wang, Wei; Zhang, Chenchen; Li, Zeshen; Gan, Xuehong
Abstract : Seismic actions inevitably cause cyclic plastic deformations in steel frame connections, which is a common cause of failure in steel structures. Nonlinear finite element (FE) static analysis has been employed in the study of the cyclic plastic behavior of a T-stub connection based on the reported cyclic test on the corresponding extensively tested T-stub connection made of Q235 steel. In particular, the isotropic-hardening and Chaboche constitutive models were employed to predict both the stress distribution and plastic development on the T-stub and the hysteretic curves of the entire T-stub connection. The two constitutive models were calibrated by four material tests to describe the yield and hardening behaviors of the Q235 steel used to make this T-stub connection. The two sets of simulation results obtained from the simulations of the two FE models employed by the two different constitutive models were compared with each other and with the experimental results. The comparisons reveal that the simulation results are similar and in good agreement with the experimental results when the cumulative plastic deformation in the T-stub is small. However, the results of the FE analysis using the Chaboche model are in better agreement with the experimental results when the cumulative deformation in the T-sub is large. This study can provide a reference for FE simulation of the cyclic plastic behavior of steel connections, including the T-stub connection.